Radiative neutrino masses in the singlet-doublet fermion dark matter model with scalar singlets (2015)
ABSTRACT: In view of the lack of signals of new physics in strong production at the LHC, there is a growing interest in simplified models where the production of new particles is only through electroweak processes, with lesser constraints from LHC limits. In particular, there are simple standard model (SM) extensions with dark matter (DM) candidates, such as the singlet scalar dark matter (SSDM) model [1–3], or the singlet-doublet fermion dark matter (SDFDM) model [4–9]. In this kind of models, the prospects for signals at the LHC are in general limited because of the softness of final SM particles coming from the small charged to neutral mass gaps of the new particles, which is usually required to obtain the proper relic density. In this sense, the addition of new particles, motivated for example by neutrino physics, could open new detection possibilities, either through new decay channels or additional mixings which increase the mass gaps.